Landscape development and climate change in southwest Bulgaria (Pirin Mountains) - Grunewald, Karsten; Scheithauer, Jörg (Springer, 2011)
Landscape Development and Climate Change in Southwest Bulgaria aims to address some of the current limitations in our understanding of past Balkan climate and environment. High mountains and their ecosystems offer an outstanding opportunity for studies on the impact of climate change. The Balkan Mountains in Southeast Europe, situated at the transition between temperate and Mediterranean climate, are considered as very sensitive to historical and current global changes. The geoarchives lake sediment, peat and soil, long living trees and glaciers have been used to reconstruct the climatically-driven change of forest and treeline during the Holocene and the younger past. These processes are interrelated with complex ecological changes, as for example the seasonality of climate parameters. The landscape research approach with the analyses through multi-palaeo-geoecological proxies is new for the Balkans.